KEKUATAN PEMBUKTIAN SAKSI MAHKOTA SEBAGAI ALAT BUKTI DALAM PEMBUKTIAN TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN - Kharisma Shalsabilla Putri Nofa; Bambang Santoso (Sebelas Maret University, 2023)
This article analyses the strength of the crown witness evidence in proving qualified theft crime in Verdict Number 342/Pid.B/2021/PN Sbr. The purpose of this article is to determine the strength of evidence of the crown witness in proving qualified theft crime. This research is normative legal research which is perspective and applied. This legal research uses a case approach. Types of legal materials used are primary and secondary legal materials. The technique of collecting legal materials used is library research. The analysis technique used is the deductive method. Based on the research results, it can be understood that the strength of evidence of the crown witness in proving qualified theft crime in Verdict Number 342/Pid.B/2021/PN Sbr is valid and accountable because it has fulfilled the requirements as evidence. As for the strength of evidence, it is independent and depends on the judge's judgment.Keywords: Strength of Evidence; Protection of the Defendant's Human Rights; Crown Witness.